2007
DOI: 10.1111/j.1467-8527.2007.00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital, Social Inclusion and Changing School Contexts: A Scottish Perspective

Abstract: :  This paper synthesises a collaborative review of social capital theory, with particular regard for its relevance to the changing educational landscape within Scotland. The review considers the common and distinctive elements of social capital, developed by the founding fathers – Putnam, Bourdieu and Coleman – and explores how these might help to understand the changing contexts and pursue opportunities for growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 23 publications
(25 reference statements)
1
19
0
Order By: Relevance
“…Alternatively, Bourdieu (1986) examined the reproduction of class advantage, regarding social capital as part of a bundle of different forms of capital, important for social injustice and equality (Field 2003;Holland, Reynolds and Weller 2007). Despite its elusive definition, there are commonalities uniting a range of authors, not least a focus on norms, trust, values and networks (Granovetter 1973;Putnam 2000;McGonigal et al 2007). This paper is framed by a broad understanding that defines social capital as the resources individuals and collectives derive from their social networks.…”
Section: Social Capital Young People and Identitymentioning
confidence: 98%
See 2 more Smart Citations
“…Alternatively, Bourdieu (1986) examined the reproduction of class advantage, regarding social capital as part of a bundle of different forms of capital, important for social injustice and equality (Field 2003;Holland, Reynolds and Weller 2007). Despite its elusive definition, there are commonalities uniting a range of authors, not least a focus on norms, trust, values and networks (Granovetter 1973;Putnam 2000;McGonigal et al 2007). This paper is framed by a broad understanding that defines social capital as the resources individuals and collectives derive from their social networks.…”
Section: Social Capital Young People and Identitymentioning
confidence: 98%
“…Parents may influence the nature of their child's social networks by seeking out schools or activities characterized by differing degrees of class-based, ethnic, gender and/or religious diversity/homogeneity (Smith and Khanom 2005;George 2007). In turn, young people can, both directly and indirectly, influence the networks of their parents and siblings (McGonigal et al 2007;Weller and Bruegel 2009).…”
Section: Researching Young People's Social Capital Over Timementioning
confidence: 98%
See 1 more Smart Citation
“…Education, as noted by McGonigal (2007, 81, citing Fukuyama 1999, 'is the area where governments have the greatest direct ability to generate … capital'. Through the lens of the discourse of inclusion, those learners with special needs who are considered 'salvagable' (Riddell et al 2001) in economic terms are gradually introduced to the various types of capital demanded by the vocational field through discreet (in-class assistance or accommodations provided by the educator) and discrete (additional funded provision addressing identified need, i.e.…”
Section: Literature Review and Personal Researchmentioning
confidence: 98%
“…The social capital of children and young people has often been overlooked in the concern for the exchanges between adults and the effects of these, but Morrow (1999, p757) reminds us that children are 'social actors who influence their own environments' and generate their own networks within school, some of which are more positive than others (McGonigal et al, 2007;Field, 2005). McGonigal et al identified a series of 'capitals' operating within schools at any given time.…”
Section: 'Open Space': Mobilising Children's Social Capitalmentioning
confidence: 99%